Integrating STEM Approach through a Student Worksheet to Strengthen Problem-Solving on the Excretory System Learning - Deva Herdina Saragih; Ummi Nur Afinni Dwi Jayanti (Universitas Labuhanbatu, 2025)
Background: The 2022 PISA assessment reveals that Indonesian students demonstrate considerably weak science problem-solving abilities, achieving merely 383 points compared to the OECD's 485-point benchmark, with this deficiency particularly pronounced in biology education where learners encounter difficulties comprehending and contextualizing concepts such as the excretory system in practical scenarios. Methodology: Employing a 4D developmental framework (Define, Design, Develop, Disseminate) truncated at the Develop phase, this investigation created a STEM-integrated student worksheet designed to strengthen problem-solving competencies among eleventh-grade pupils, utilizing expert validation, stakeholder feedback surveys, and pre-post assessment protocols analyzed through percentage calculations, N-Gain coefficients, and paired-samples t-testing. Findings: The intervention demonstrated exceptional validity with 90% expert approval ratings across content and pedagogical dimensions, exhibited strong practicality reflected in 88.71% positive educator-student reception, and yielded statistically significant learning gains as evidenced by paired t-test results (p < 0.05) alongside a substantial N-Gain value of 0.75. Contribution: This study provides specific empirical evidence that a STEM-integrated student worksheet, developed through an adapted 4D model, effectively strengthens eleventh-grade students’ science problem-solving abilities in the excretory system Learning. The results further contribute to the field by establishing this worksheet as a valid, practical, and statistically proven instructional alternative that aligns with competency-based demands and improves analytical reasoning more effectively than conventional learning materials